Comparative Research between the science of Mythology and Archeology - Mawlud Ibrahim Hassan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
This study, under the title "the Sanhareeb Project of Erbil between Mythology and Archeology", is an analytical and comparative research. Today, sciences tend to approach each other and relations between them more shout out, including the humanities and the scientific experiments. This is due to the fact that it is human being who invents and coins these sciences and utilizes them as well. In the realms of time, these sciences are the products of human brain, and thus, the human mind is the centre of all thinking and processing in relations to sciences. Mythology and archeology, as such, are two very ancient and authentic fields of human knowingness, and in that term there is a deep connection between them, or even they complete one and another. This paper attempts to find out that strong tie between Sanhareeb Water Project of Erbil- 681 B.C. and the myth of the Lovers’ Stream. Also, it focuses on their mythical contrasts. This study affirms the logic that myth, in many cases, reaffirm the historical facts, and in many other cases, figures new things out. These upheavals undergo the categories of personality, place, time and event. In addition, myth is known to have always been on a track side of reality and the status quo; therefore, they can complete one another. However, myth has a special language of narration, which can be sometimes code-based and full of connotation. Besides, Myth changes time, place, personalities and incidents. That is why a scholar of mythology has to be alert and cautious. The writer of the present research, through the use of comparative-analytical method, has afforded to establish the connections between mythology and archeology in Sanhareeb Water Project and the myth of the Lovers’ Stream. Consequently, some suggestions are proposed to the experts and the elite of both fields, so that afterwards the Kurdish experts will pay more attention to such ideas, and they will serve the Kurdish culture and community more.